TRAF3IP3 Is Cleaved by EV71 3C Protease and Exhibits Antiviral Activity - Li, Hui; Yao, Yunfang; Chen, Yu; Zhang, Shuangling; Deng, Zhi; Qiao, Wentao; Tan, Juan (Frontiers in Microbiology, 2022)
Enterovirus 71 (EV71) is one of the major pathogens of hand, foot, and mouth disease, which poses a major risk to public health and infant safety. 3C protease (3Cpro), a non structural protein of EV71, promotes viral protein maturation by cleaving polyprotein precursors and facilitates viral immune escape by cleaving host proteins. In the present study, we screened for human proteins that could interact with EV71 3Cpro using a yeast two-hybrid assay. Immune-associated protein TRAF3 Interacting Protein 3 (TRAF3IP3) was selected for further study. The results of co-immunoprecipitation and immunofluorescence demonstrated the interaction between TRAF3IP3 and EV71 3Cpro. A cleavage band was detected, indicating that both transfected 3Cpro and EV71 infection could cleave TRAF3IP3. 87Q-88G was identified as the only 3Cpro cleavage site in TRAF3IP3. In Jurkat and rhabdomyosarcoma (RD) cells, TRAF3IP3 inhibited EV71 replication, and 3Cpro cleavage partially resisted TRAF3IP3-induced inhibition. Additionally, the nuclear localization signal (NLS) and nuclear export signal (NES) of TRAF3IP3 were identified. The NES contributed to TRAF3IP3 alteration of 3Cpro localization and inhibition of EV71 replication. Together, these results indicate that TRAF3IP3 inhibits EV71 replication and 3Cpro resists such inhibition via proteolytic cleavage, providing a new example of virus-host interaction.